2012
DOI: 10.3354/dao02537
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary ultrasound findings in a bottlenose dolphin Tursiops truncatus population

Abstract: Lung disease is common among wild and managed populations of bottlenose dolphins Tursiops truncatus. The purpose of the study was to apply standardized techniques to the ultrasound evaluation of dolphin lungs, and to identify normal and abnormal sonographic findings associated with pleuropulmonary diseases. During a 5 yr period (2005 to 2010), 498 non-cardiac thoracic ultrasound exams were performed on bottlenose dolphins at the Navy Marine Mammal Program in San Diego, California, USA. Exams were conducted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…In contrast to the slowly improving prevalence of moderate to severe lung disease was the increased proportion of AIS among BB dolphins in 2013−2014 and MS dolphins in 2013. Smith et al (2012) reported ultrasound evidence of AIS as consistent with pneumonia, pulmonary edema, and pulmonary fibrosis in dolphins. These findings could be secondary to an oil-induced injury.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast to the slowly improving prevalence of moderate to severe lung disease was the increased proportion of AIS among BB dolphins in 2013−2014 and MS dolphins in 2013. Smith et al (2012) reported ultrasound evidence of AIS as consistent with pneumonia, pulmonary edema, and pulmonary fibrosis in dolphins. These findings could be secondary to an oil-induced injury.…”
Section: Discussionmentioning
confidence: 97%
“…Pulmonary damage and subsequent respiratory compromise would not be unusual for mammals several years following exposure to an oil spill. In fact, acute and chronic respiratory symptoms were reported in humans following inhalation exposure from multiple spills, including the Prestige, Hebei Spirit, Tasman Spirit, and DWH oil spills (Suárez et al 2005, Carrasco et al 2006, Janjua et al 2006, Zock et al 2007, 2012, Sim et al 2010, Jung et al 2013, Sandler et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations